EXPECTATIONS AND RATIONAL DECISIONS ACCORDING TO JOHN MAYNARD KEYNES’S THOUGHT - MORSELLI, Alessandro (Theoretical and Practical Research in Economic Fields; Vol 8 No 2 (2017): TPREF, Volume VIII, Issue 2(16), Winter 2017, 2017)
The aim of this paper is to question the existence of economic laws that can uniquely determine capitalist “equilibrium”. The presence of uncertainty is one of the conditions that cannot be eliminated, which can make the equilibrium unstable. We will try to find possible improvements in the techniques of modern capitalism through collective action, beyond the rationale of “laissez-faire”. All this in a Keynesian methodological view and in the presence of a social pact which, by committing the parties to the attainment of collective goals, minimizes the conflict. If a separation between spending decisions and savings decisions is assumed, the role of an external subject that can affect the current and expected profitability is particularly important. Thus, this issue will be addressed, that is, the expectation of profit in a system of uncertainties, where well-governed capitalism can represent the closest frame to the most efficient system to achieve economic goals.